2011
DOI: 10.1590/s2237-93632011000400011
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of rectal leiomyoma by endoscopic resection

Abstract: Leiomyomas of the rectum are rare, with low reported incidence in literature. In most cases, patients are asymptomatic, and are often incidental endoscopic findings. The difficult distinction from leiomyosarcomas, associated with the possibility of recurrence, implies the absence of a standard treatment. Endoscopic resection, if well indicated, may be a therapeutic option. In this study, we report two cases of asymptomatic leiomyoma of the rectum in two patients, discovered incidentally during a routine colono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Overall, leiomyomas comprise about 0.03 to 0.05% of all rectal tumors. 6 While they are more common in women, there is data showing that leiomyomas of the gastrointestinal tract are more prevalent in males. A study done in 2001 evaluated a total of 88 patients in two institutions with confirmed leiomyoma of the rectum or colon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, leiomyomas comprise about 0.03 to 0.05% of all rectal tumors. 6 While they are more common in women, there is data showing that leiomyomas of the gastrointestinal tract are more prevalent in males. A study done in 2001 evaluated a total of 88 patients in two institutions with confirmed leiomyoma of the rectum or colon.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic modalities include colonoscopy, endoscopic ultrasound (EUS), computed tomography and magnetic resonance of the rectum. 6 After screening with colonoscopy, EUS is uniformly preferred over the aforementioned modalities. A cohort of 80 patients diagnosed with rectal cancer, showed that EUS was more accurate than CT in staging rectal carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Most leiomyomas are incidental findings in cancer or polyp surveillance programmes and, like perineurioma, are less than 10 mm in size . They can be seen endoscopically as both intramural and sessile or pedunculated intraluminal masses . Clinical manifestations include rectal bleeding, pain, obstruction and even perforation into the peritoneal cavity .…”
Section: Leiomyomamentioning
confidence: 99%
“…The peak incidence occurs in the third decade of life with a slight female predominance[2]. Colonic leiomyomas are usually asymptomatic and are detected incidentally during screening colonoscopy[5][6][7][8].…”
mentioning
confidence: 99%